Issue Competition in Parliamentary Speeches? A Computer-based Content Analysis of Legislative Debates in the Austrian Nationalrat - Christoph Ivanusch (Legislative Studies Quarterly, 2024)
Parliamentary speeches are an important communication channel for political parties. A growing amount of literature suggests that parties use them to send policy signals in party competition. Although this perspective has become more popular in the literature, there is a lack of studies that focus on issue competition. I take a step towards closing this research gap by using a text-as-data approach to analyze parliamentary speeches in the Austrian Nationalrat. The data set consists of more than 56,700 speeches given by MPs between 2002 and 2019. I apply a semi-supervised technique to classify the speeches at sentence level into 20 issue categories. The analysis shows that, despite the constraining parliamentary context (e.g., legislative agenda), parties put comparatively strong emphasis on their issue preferences. The magnitude of this effect, however, depends on a party's legislative agenda-setting power. These findings confirm the presence and specific nature of issue competition in parliamentary speeches.
https://doi.org/10.7910/DVN/YXXWQG
Keywords: 320; issue competition; parliamentary speeches; political parties; text-as-data; Nationalrat